2021
DOI: 10.1302/2058-5241.6.200120
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of venous thromboembolism with aspirin following knee surgery: A systematic review and meta-analysis

Abstract: Venous thromboembolism (VTE) is a well-known complication following orthopaedic surgery. The incidence of this complication has decreased substantially since the introduction of routine thromboprophylaxis. However, concerns have been raised about increased bleeding complications caused by aggressive thromboprophylaxis. Attention has grown for aspirin as a safer thromboprophylactic agent following orthopaedic surgery. A systematic review using MEDLINE, Embase and Web of Science databases was undertaken to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 73 publications
0
8
0
7
Order By: Relevance
“…La RS más actual y con el mayor número de estudios incluidos [10] tuvo 32 de 50 ECA, un (64 %) del total para ser elegibles de acuerdo a los criterios de selección del trabajo. Se exploró si esta revisión excluyó explícitamente estos estudios o si hubo criterios adicionales que explicaran por qué no se incluyeron.…”
Section: Resultsunclassified
“…La RS más actual y con el mayor número de estudios incluidos [10] tuvo 32 de 50 ECA, un (64 %) del total para ser elegibles de acuerdo a los criterios de selección del trabajo. Se exploró si esta revisión excluyó explícitamente estos estudios o si hubo criterios adicionales que explicaran por qué no se incluyeron.…”
Section: Resultsunclassified
“…Therefore, when using LMWH for thrombosis prevention, clinicians should closely monitor the changes in Hb decline and post-treatment drainage volume in patients, promptly replenish blood volume according to the patient condition, and provide other symptomatic supportive treatments. As indicated in the meta-analysis carried out by Marannes et al [ 35 ], Xa I was more effective than ASA, LMWH, and warfarin on preventing VTE after TKA, but it was associated with a significantly increased bleeding complication rate. Zou et al [ 18 ] compared the efficacy and safety of ASA, RA, and LMWH in the prevention of DVT after TKA.…”
Section: Discussionmentioning
confidence: 99%
“…81,83 Marrannes et al in their meta-analysis did not find a significant difference in DVT/PE rates following TKA based on dosage differences in aspirin. 84 In relation to VTE prophylaxis in patients weighing 120 kg, a higher dose of aspirin (320 mg twice daily) was shown to result in over 60% reduction in VTE incidence up to 6 months following surgery, when compared with 81 mg twice daily. 85 However, another smaller study showed no difference in 90-day VTE rates with either of these doses between BMI categories.…”
Section: Doacsmentioning
confidence: 99%
“…81 83 Marrannes et al in their meta-analysis did not find a significant difference in DVT/PE rates following TKA based on dosage differences in aspirin. 84…”
Section: Pharmacological Thromboprophylaxis In Obesity: Dosing Princi...mentioning
confidence: 99%